The Importance of Ubiquitination and Deubiquitination in Cellular Reprogramming - Bharathi Suresh; Junwon Lee; Kye-Seong Kim; Suresh Ramakrishna (Stem Cells International)
Ubiquitination of core stem cell transcription factors can directly affect stem cell maintenance and differentiation. Ubiquitination and deubiquitination must occur in a timely and well-coordinated manner to regulate the protein turnover of several stemness related proteins, resulting in optimal embryonic stem cell maintenance and differentiation. There are two switches: an E3 ubiquitin ligase enzyme that tags ubiquitin molecules to the target proteins for proteolysis and a second enzyme, the deubiquitinating enzyme (DUBs), that performs the opposite action, thereby preventing proteolysis. In order to maintain stemness and to allow for efficient differentiation, both ubiquitination and deubiquitination molecular switches must operate properly in a balanced manner. In this review, we have summarized the importance of the ubiquitination of core stem cell transcription factors, such as Oct3/4, c-Myc, Sox2, Klf4, Nanog, and LIN28, during cellular reprogramming. Furthermore, we emphasize the role of DUBs in regulating core stem cell transcriptional factors and their function in stem cell maintenance and differentiation. We also discuss the possibility of using DUBs, along with core transcription factors, to efficiently generate induced pluripotent stem cells. Our review provides a relatively new understanding regarding the importance of ubiquitination/deubiquitination of stem cell transcription factors for efficient cellular reprogramming.